2010
DOI: 10.1080/19406941003634024
|View full text |Cite
|
Sign up to set email alerts
|

Elite athletes and university education in Europe: a review of policy and practice in higher education in the European Union Member States

Abstract: This article provides an analysis of the ways in which European Union Member States have sought to address the educational needs of elite young sportspersons. Drawing on fieldwork by 25 research teams led by the authors and undertaken on behalf of the European Commission, it reflects the European Union's increasing concern with protection of the rights of young athletes. Our focus in this paper is on higher education and its adaptation to accommodate the delivery of education to elite athletes. The review of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
145
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 13 publications
4
145
0
13
Order By: Relevance
“…On the contrary, in Europe, the relationships between sport and educational systems are not still well established [3], favouring talented athletes' sport dropout to prioritize education to prepare for future job opportunities [13,14] or to postpone (i.e., [24 years of age) the achievement of a degree. In this framework, among European countries, Italy was classified [15] into the laisser-faire/no formal structure category, which is characterized by the absence of support policies toward student-athletes' dual career, determining the need of individual negotiations between athletes and the teaching staff for a flexible academic path. Although several universities have implemented their dual career structures and/ or established agreements with national sports federations [4], interventions are still restricted to a particular academic/sports environment and involving only a limited number of elite athletes at national level.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in Europe, the relationships between sport and educational systems are not still well established [3], favouring talented athletes' sport dropout to prioritize education to prepare for future job opportunities [13,14] or to postpone (i.e., [24 years of age) the achievement of a degree. In this framework, among European countries, Italy was classified [15] into the laisser-faire/no formal structure category, which is characterized by the absence of support policies toward student-athletes' dual career, determining the need of individual negotiations between athletes and the teaching staff for a flexible academic path. Although several universities have implemented their dual career structures and/ or established agreements with national sports federations [4], interventions are still restricted to a particular academic/sports environment and involving only a limited number of elite athletes at national level.…”
Section: Introductionmentioning
confidence: 99%
“…Trainers and other professionals in the area of trainings and education, state-of-the-art sports infrastructure and scholarships for study programmes are available to them while they compete for their universities; nevertheless, the student-athletes strive for good grades (Gatmen, 2012) and are usually motivated to achieve good sports results (Gaston-Gayles, 2005). On the opposite, in the European Union member states the elite sport more or less depends on small private clubs and national sports associations with basically no connections to the education system (Aquilina & Henry, 2010;Stambulova, Stephan, Jäphag, 2007). Consequently, young athletes are confronted with considerable difficulties when coordinating their dual careers (Brettschneider, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this, each EU member state takes decisions on the implementation of these guidelines autonomously in line with its financial situation and development strategy. In their research that analysed 25 EU member states, Aquilina and Henry (2010) identified four approaches to the academic education of the elite athletes. At the same time, they established that several states do not take any of the identified approaches.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años son numerosas las investigaciones a nivel internacional que se centran en analizar las principales variables que influyen en la carrera dual de estudiantes deportistas, es decir, en la conciliación de la carrera académica y deportiva (Aquilina & Henry, 2010;Debois, Ledon & Wylleman, 2015;Ryba, Stambulova, Ronkainen, Bundgaard & Selänne, 2015;Stambulova, Engtröm, Franck, Linnér & Lindahl, 2014;Tshube & Feltz, 2015;Wylleman, Alfermann & Lavallee, 2004). Entre los factores que pueden facilitar su unión destacan los recursos internos (características personales, percepción de competencia, autonomía, motivación) y los recursos externos (apoyo social en el ámbito familiar, deportivo y académico) (Alfermann & Stambulova, 2007;Guidotti, Lupo, Cortis, Di Balsasagre & Capranica, 2014;Lenténé & Perényi, 2015).…”
Section: Introductionunclassified
“…A nivel europeo existen programas que persiguen implantar las principales directrices que optimizan la carrera dual (Comisión Europea, 2012). También numerosas universidades establecen programas propios de apoyo a los estudiantes deportistas (Álvarez et al, 2012;Aquilina et al, 2010;Conde, 2013;Mateos, Torregrosa & Cruz, 2010). Sin embargo, hoy en día, una de las mayores incógnitas que giran en torno a la carrera dual es conocer qué modelo se podría aplicar para optimizar la armonización de ambas carreras, puesto que, tal como indicaron Álvarez et al (2012), es necesario un trato individualizado que permita gestionar la alternancia de esta doble actividad.…”
Section: Introductionunclassified